Energetically distinct early and late stages of HlyB/HlyD-dependent secretion across both Escherichia coli membranes. - Koronakis, V (1991)
The alternative secretion pathway which exports hemolysin across both Escherichia coli membranes into the surrounding medium is directed by an uncleaved C-terminal targeting signal and the membrane translocator proteins HlyD and HlyB. In order to identify stages and intermediates in this unconventional secretion process we have examined the effect of inhibition of the total proton motive force (delta P) and its components during the in vivo HlyB/HlyD-dependent export of a 22.4 kDa secretion competent HlyA C-terminal peptide (Actp). Secretion of Actp was severely inhibited by the proton ionophore carbonylcyanide m-chlorophenylhydrazone (CCCP), which collapses simultaneously membrane potential delta psi and the proton gradient delta pH, and also by valinomycin/K+, a potassium ionophore which disrupts delta psi. The inhibition of secretion by valinomycin/K+ was ameliorated by imposition of a pH gradient, the second component of the delta P, and selective depletion of delta pH by nigericin also blocked secretion. This indicates that, as in the secretion of beta-lactamase to the periplasm, HlyB/D-directed secretion requires delta P itself and not specifically one of its components. However, inhibition of HlyB/D-dependent secretion was only marked when CCCP, valinomycin/K+ or nigericin were present during the early stage of Actp secretion; at a later stage the secretion was not significantly inhibited. HlyB/D-dependent secretion appears therefore to share with conventional secretion across the cytoplasmic membrane an early requirement for delta P, but comprises in addition a late stage which does not require delta P, delta psi or delta pH. The translocation intermediate identified in the delta P-independent late stage of secretion was associated with the membrane fraction. Analysis of the protease accessibility of this intermediate in whole cells and spheroplasts showed that it was not in the periplasm, nor was it exposed on the cell surface or on the periplasmic faces of either the inner or outer membranes. This may reflect its close association with the inner membrane or a membrane translocation complex.